Pengaruh Luas Lahan dan Produksi CPO Terhadap Pertumbuhan Industri Kelapa Sawit Indonesia Tahun 2000-2020 - Atikah Atikah; Sumaryoto Sumaryoto; Darwati Susilastuti (eCo-Buss, 2022)
This study aims to analyze the effect of economic indicators including land area and palm oil (CPO) production on the growth of the palm oil industry in Indonesia. Data on land area variables includes all land planted with oil palm, both smallholder plantations, large state plantations and large private plantations. This study uses secondary data with a time span of 21 (Twenty One) years, namely from 2000-2020. The method used in this research is descriptive and verification method with a quantitative approach. The population of this study includes the six largest palm oil producing provinces in Indonesia, namely Riau, Central Kalimantan, West Kalimantan, North Sumatra, East Kalimantan and Jambi. Thus, the sample size used in this study is 6 provinces times 21 years, namely 126 panel data samples using the Random Effect Model (REM) model. This study uses data processing software Eviews 12. The results of this study indicate that the variables of land area and production of palm oil (CPO) together have a positive and significant effect on the growth of the Indonesian palm oil industry. If tested partially, the area of ????oil palm plantations is significant and has a positive influence on the growth of the Indonesian palm oil industry. However, CPO production has a negative effect on the growth of the Indonesian palm oil industry.